Representasi Toleransi Dalam Lirik Lagu Peradaban Karya Grup Musik .Feast - Tri Adhyatmika, I Gede Nyoman Arya; Sugiarica Joni, I Dewa Ayu; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2019)
ABSTRACT This research contains the representation of tolerance meaning in the lyrics of “Peradaban” song by the .Feast music group. This research uses the semiotic theory of Ferdinand De Saussure. The Saussure Semiotic theory explains that sign has an interrelated element, namely a marker (signifier) and a sign (signified), then obtained a meaning or significance. This process connects the lyrics of “Peradaban” song with the real external world. The result of this research, the lyrics contains interrelated meanings about the importance of tolerance. Songwriters make very complex song lyrics, describe conflict, human attidudes and hope that are inserted at the end them. The theoriatical model of Ferdinand De Saussure focuses directly on the sign itself. In this research, the researcher divided the entire song lyrics into several verses and the analyzed the using the semiotic theory of Ferdinand De Saussure. Keywords : .Feast, Ferdinand De Saussure, Semiotics, Song Lyrics, Tolerance